Mastering Qlik Sense - Bhosle, Diksha (Packt Publishing, 2019)
"You've probably done some beginner work on Qlik Sense, so you know how easy it is to work with the interface. However, there is always more than what we see on the Qlik Sense dashboard. Work done by developers in the extremity plays a very important role while making an appealing and well-performing dashboard. If your data model is not designed appropriately, you will face issues not only with the performance of the app but also with the quality of its output. In this course, we look at everything that goes into creating a data model to give you the most optimized performance, including how to load data from different data sources, fix synthetic keys, and other issues. Also included are topics such as creating link tables, the master calendar script, and applying set analysis to your data. Thus, you will master the art of creating dashboards that are not only visually appealing and accurate but also very informative and a BIG bonus to your team while making those tough decisions."--Resource description page